2003
DOI: 10.1038/sj.cgt.7700670
|View full text |Cite
|
Sign up to set email alerts
|

Role of 4-1BB:4-1BB ligand in cancer immunotherapy

Abstract: The activation of T cells plays a central role in antitumor immunity. In order to activate naïve T cells, two key signals are required. Signal one is provided through the T-cell receptor (TCR) while signal two is that of costimulation. The CD28:B7 molecules are one of the best-studied costimulatory pathways, thought to be the main mechanism through which primary T-cell stimulation occurs. However, a number of molecules have been identified which serve to amplify and diversify the T-cell response, following ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
98
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 84 publications
0
98
0
Order By: Relevance
“…6 IL-15 is essential for the development and function of NK cells. 7 Coculture of NK cells with K562 cells ectopically coexpressing 4-1BB ligand (4-1BBL) and membrane-bound IL-15 effectively promotes the expansion of NK cells in vitro and mediates their cytotoxicity against some leukemia cells.…”
Section: Introductionmentioning
confidence: 99%
“…6 IL-15 is essential for the development and function of NK cells. 7 Coculture of NK cells with K562 cells ectopically coexpressing 4-1BB ligand (4-1BBL) and membrane-bound IL-15 effectively promotes the expansion of NK cells in vitro and mediates their cytotoxicity against some leukemia cells.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, IL-15 holds great potential for combination therapies. 4-1BB is a costimulatory member of the TNF receptor superfamily (TNFR-SF) that is upregulated on activated T cells and NK cells (19). Costimulation by 4-1BBL/4-1BB interaction is fundamentally involved in the proliferation, differentiation, and survival of CD8 þ T cells, therefore thought to play an important role in potentiating cytotoxic T-cell immune responses (20).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, K32/CD3/28 cells promoted the expansion of CD4 + T cells whereas failed to support long-term growth of CD8 + T cells. 4-1BB stimulation preferentially activated CD8 + T cells in vitro and amplified generation of CTL responses in vivo (28,29). It was shown that the addition of 4-1BB co-stimulation not only could promote CD8 + T cell proliferation, but also overcome activation-induced non-responsiveness to increase IL-2 and Bcl-xL expression and survival of CD8 + T cells (3).…”
Section: Discussionmentioning
confidence: 99%